Two new species of Gastrodia (Gastrodieae, Epidendroideae, Orchidaceae) from Okinawa Island, Ryukyu Islands, Japan - Suetsugu, Kenji (Phytotaxa, 2017)
Two new mycoheterotrophic orchids, Gastrodia nipponicoides and G. okinawensis, are described and illustrated from Okinawa Island, Ryukyu Islands, Japan. The outline floral shape of Gastrodia nipponicoides indicates a close affinity to G. nipponica, but it is easily distinguished from G. nipponica by several characteristics such as a shorter perianth tube, lack of rostellum and fewer ridges on its lip. Gastrodia okinawensis is similar to G. takeshimensis but is distinguished by having chasmogamous flowers, paler perianth tube and longer column.